Women`s swimming sprint elite's key anthropometrics (body mass and length) analysis by events, styles and age/ fitness periods - Gilev, G. A.; Vladykina, V. V.; Pleshakov, A. A.; Belyaev, V. V.; Zubko, E. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to profile the age-, body-length and mass-specific variations in the women`s swimming sprint elite by events, swimming styles and fitness stages.